2002
DOI: 10.1038/sj.ijo.0801874
|View full text |Cite
|
Sign up to set email alerts
|

The effect of graded levels of exercise on energy intake and balance in free-living women

Abstract: Markedly increasing EE through exercise produced significant but partial compensations in EI ( approximately 33% of EE due to exercise). Accurate adjustments of El to acute increases in EE are likely to take weeks rather than days.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
144
4
5

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(161 citation statements)
references
References 11 publications
8
144
4
5
Order By: Relevance
“…17 However, Westerterp and Goran 18 recruited women aged 19-49 and Paul et al 17 recruited women with an average age of 48 ± 10 years. When Stubbs et al 20 increased energy expenditure over a period of 7 days by implementing 80 min of exercise per day in women aged 23 ± 0.6 years, they did not find any compensation in energy intake. This suggests that whether or not women compensate their energy intake to meet energy expenditure may depend on age.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…17 However, Westerterp and Goran 18 recruited women aged 19-49 and Paul et al 17 recruited women with an average age of 48 ± 10 years. When Stubbs et al 20 increased energy expenditure over a period of 7 days by implementing 80 min of exercise per day in women aged 23 ± 0.6 years, they did not find any compensation in energy intake. This suggests that whether or not women compensate their energy intake to meet energy expenditure may depend on age.…”
Section: Introductionmentioning
confidence: 90%
“…As described earlier, the discrepancy between genders in the association between body composition and physical activity-related energy expenditure shown in previous studies was concluded to result from an increased energy intake to compensate for a higher energy expenditure in women compared with men. 18 Given that in young women, no compensation in energy intake was shown in response to an increase in energy expenditure, 20 we hypothesized an age effect for this compensatory mechanism. This hypothesis is affirmed by the association between body composition and physical activity shown in the present study.…”
Section: Body Composition and Physical Activitymentioning
confidence: 99%
“…When extending daily exercise to weeks or months, sex differences in energy intake have been noted in some but not all studies. In a series of studies, Stubbs and colleagues [71,72] showed that there was no compensation in energy intake with 7 days of exercise in men. In contrast, women partially compensate by increasing energy intake (+33 %) in response to the same 7 days of exercise.…”
Section: Exercise and Ad Libitum Energy Intakementioning
confidence: 99%
“…This is of clinical, as well as mechanistic, importance as adult individuals often increase energy intake when they exercise, 11,12 thus compensating for the extra energy deficit caused by exercise. Overweight and obese middle-aged men, with an increased waist circumferenceFa group at increased risk of cardio-metabolic disease, who are typically targeted with exercise for health interventionsFwere chosen for the study.…”
Section: Introductionmentioning
confidence: 99%